Mechanisms underpinning protection against eccentric exercise-induced muscle damage by ischemic preconditioning. (January 2017) - Franz, Alexander; Behringer, Michael; Nosaka, Kazunori; Buhren, Bettina Alexandra; Schrumpf, Holger; Mayer, Constantin; Zilkens, Christoph; Schumann, Moritz
Abstract: Eccentric exercise training is effective for increasing muscle mass and strength, and improving insulin sensitivity and blood lipid profiles. However, potential muscle damage symptoms such as prolonged loss of muscle function and delayed onset of muscle soreness may restrict the use of eccentric exercise, especially in clinical populations. Therefore, strategies to reduce eccentric exercise-induced muscle damage (EIMD) are necessary, and an extensive number of scientific studies have tried to identify potential intervention modalities to perform eccentric exercises without adverse effects. The present paper is based on a narrative review of current literature, and provides a novel hypothesis by which an ischemic preconditioning (IPC) of the extremities may reduce EIMD. IPC consists of an intermittent application of short-time non-lethal ischemia to an extremity (e.g. using a tourniquet) followed by reperfusion and was discovered in clinical settings in an attempt to minimize inflammatory responses induced by ischemia and ischemia-reperfusion-injury (I/R-Injury) during surgery. The present hypothesis is based on morphological and biochemical similarities in the pathophysiology of skeletal muscle damage during clinical surgery and EIMD. Even though the primary origin of stress differs between I/R-Injury and EIMD, subsequent cellular alterations characterized by an intracellular accumulation of Ca 2+, an increased production of reactive oxygen species or increased apoptotic signaling are essential elements for both. Moreover, the incipient immune response appears to be similar in I/R-Injury and EIMD, which is indicated by an infiltration of leukocytes into the damaged soft-tissue. Thus far, IPC is considered as a potential intervention strategy in the area of cardiovascular or orthopedic surgery and provides significant impact on soft-tissue protection and downregulation of undesired excessive inflammation induced by I/R-Injury. Based on the known major impact of IPC on skeletal muscle physiology and immunology, the present paper aims to illustrate the potential protective effects of IPC on EIMD by discussing possible underlying mechanisms.